A systematic review of the determinants of the nutritional quality of food for homeless populations. (20th October 2021) - Ravikumar, D; Nic Gabhann, S; Kelly, C
Abstract: Introduction: Studies assessing the nutritional quality of food provided to homeless population show deficiencies in micronutrients and excess fat, sugar and salt. The availability of cheap, energy-dense and nutrient poor food has changed the profile of people living with homelessness from primarily underweight to obese in western countries. Many factors influence the nutritional quality of food provided to the homelessness population such as budget and time constraints, food donations and limited equipment. Nutrient intakes in this population are unlikely to be met outside of charitable meal programmes, making the nutritional quality of these meals crucial. This review will synthesise qualitative literature with the aim of understanding of the determinants of the nutritional quality of food provided to the homeless population. Methods: This qualitative evidence synthesis will include English language primary research empirical studies from Europe, North America and Oceania. Searches will be conducted on Web of Science, CINAHL, Embase, Scopus, PsycINFO, Google Scholar, OpenGrey and ProQuest. Quality appraisal will be conducted using the Standards for Reporting Qualitative Research tool. Two independent reviewers will be included in study selection, data extraction and quality appraisal. A third reviewer will resolve conflicts. Results: Demographic data on study participants and findings and quotations will be extracted. Thematic synthesis will be employed. Results will be organised based on a determinants of health model, to highlight areas where change may be effective, thereby making it more likely to be useful to practitioners and researchers. The iterative steps in the systematic review process will be the focus of this presentation. Conclusions: Findings from this review will be used to develop best-practice guidelines for policy makers and service providers to improve the nutritional quality of food provided in the homeless sector. Key messages: The determinants of the nutritional quality of food provided to the homeless population are influenced by multiple factors. This review will provide a comprehensive assessment of these determinants. This presentation will detail the iterative steps undertaken to conduct this systematic review.